Pemanfaatan IoT untuk Mendeteksi Dini Kelembaban Kamar Hotel - Dedy Irawan, Joseph; Primaswara Prasetya, Renaldi; Limpraptono, Yudi (Universitas Merdeka Malang, 2022)
The pandemic period has greatly affected various business sectors which also resulted in the decreasing income of most people. This is coupled with the implementation of PPKM (Enforcement of Restrictions on Community Activities) in several areas, so that community activities are very limited. One of the impacts of this pandemic is being felt in the hotel business, where many hotels and inns are not selling well and this business has to go out of business. Hotels and inns that can still survive are forced to reduce the number of employees and reduce operational costs, one of which is the cost of room maintenance. Along with the number of vacant rooms due to lack of customers and reduced number of employees, resulting in vacant rooms are rarely opened which will become damp and stuffy. If this is left for a long time will result in the growth of mold in the hotel room, so a process of monitoring temperature and humidity is needed. These problems can be solved by utilizing the Internet of Things (IoT). From the results of testing the temperature and humidity sensor readings using DHT11, the results are quite accurate with an error rate of 1.30% for measuring temperature and 3.79% for measuring humidity. Making an IoT system using Blynk can be done very easily because it does not require programming skills in its manufacture.